Perancangan Alat Pemberian Pakan Ikan Otomatis Pada Aquarium Berbasis Mikrokontroller AT89S52 - Wijaya, I Gusti Ngurah Bagus Agung Brian; Putra, Ida Ayu Gde Suwiprabayanti (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
An important factor in keeping fish in an aquarium is the timeliness of feeding fish. Most of those who have a hobby of raising fish are worried about the feeding that must be done every day.Based on this, this final project designed and manufactured an automatic fish feeding device based on the AT89S52 microcontroller. So, a tool was designed that makes it easier to feed the fish automatically according to a predetermined schedule. The supporting components for scheduling fish feed include making a minimum circuit for the AT89S52 system as the brain of this tool which will later be loaded with a program using assembler language, RTC (Real Time Clock) as a timer, DC motor to rotate the valve opener for fish feed.